Pengelolaan Sampah Di Kota Tanjungpinang - Sabrina Swara; Muhammad Rafly Zakri; Syafiq Ramadhan (CV. ITTC INDONESIA, 2026)
This study aims to analyze the waste management system in Tanjungpinang City and the innovations made by the Ganet Landfill Technical Implementation Unit (UPTD) in reducing environmental pollution. The main problem faced is the increasing amount of waste along with population growth, which has an impact on the landfill's capacity. This study uses a qualitative descriptive approach by examining the waste management process from collection, transportation, sorting, to final processing. The results show that waste management at the Ganet landfill has implemented various innovations such as composting, processing plastic waste into fuel through pyrolysis, and utilizing methane gas as an alternative energy source. In addition, waste reduction programs such as waste banks and community outreach also support waste control efforts. However, the continuous increase in waste volume poses a challenge to the sustainability of the existing management system. Therefore, it is necessary to strengthen policies, increase community participation, and develop sustainable innovations in waste management in Tanjungpinang City.